Enfermera-matrona: beneficios, competencias e intervenciones - Ruth Alexandra Castiblanco-Montañez; Diana Camila Berruecos-Prada; Esmeralda María Calderón-Rivas; Mary Julieth Guayacundo-Aldana; Ruby Magdaly Mancera-García; Karen Sofía Rodríguez-Ramírez (Universidad Francisco de Paula Santander, 2021)
Introduction: Nurse-midwifery allows expectant mothers to have autonomy during their pregnancy and birth, but it is not currently recognized as a profession; however, the legal resolution 3280 of 2018 defines the technical and operational guidelines of the Comprehen-sive Health Care Pathways for the Maternal and Perinatal Health Population and establishes their operational guidelines, emphasizing the participation of the nursing professional in the preconception consultation and prenatal care. Objective: Recognize the benefits of the care provided by nurses during the pregnancy and labor reported in the literature. Methodolo-gy: Comprehensive review of the literature with a searching period between February-May of 2020 in the EBSCO, Pubmed, LILACS, Cuiden and Google Scholar databases with the following DeCS-MeSH terms: Midwifes, complications, labor, pregnancy, nursing care and postpartum period, logical connectors AND-OR. 44.966 papers in English, Spanish and Por-tuguese were obtained and grouped according to their title, abstract, full text, level of evi-dence and level of recommendation; however, 33 of these papers were chosen for critical reading. It should be made clear that the ethical considerations were met for documentary research. Results: Through the analysis of the content 4 topics were built: benefits of prenatal care and assisted delivery, abilities and interventions of the nurse for the comprehensive care of the expectant mother, risk considerations of the nurse during prenatal care and delivery and nursing care challenges during the pregnancy, labor and postpartum period. Conclusion: The assistance of the nurse during low-risk pregnancies provides multiple benefits for the woman, reduces the pain and period of labor; also enabling the identification of risks in a timely manner.